Hybridity in Transitional Justice: Legacy of The “Khmer Rouge Tribunal” - Danijel Apro; Sudarmo Sudarmo (Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractCountries throughout the world practice several forms of transitional justice, hoping to attain peace, democratic stability and reconciliation. They apply different mechanisms to achieve these goals. Thispaper offers a theoretical analysis of foundation, proceedings and legacy of the Extraordinary hambersin the Courts of Cambodia (ECCC). First, the Author examines the notion of the analysis of hybrid courts as a way of overcoming constraints that criminal justice mechanisms in post-conflict societies may face. Second, the Author explores the so-called “Khmer Rouge Tribunal”. Due to the significance and controversies that surround the ECCC, its work attracts great attention. Furthermore, political will is critical, so these hybrid judicial institutions should have more international support in terms of political means, funds, dissemination of results, and complementary mechanisms of transitional justice.IntisariNegara-negara di seluruh dunia mempraktikkan beragam bentuk keadilan transisional, dengan harapan untuk memelihara perdamaian, stabilitas demokrasi, dan rekonsiliasi. Mereka menerapkan mekanisme yang berbeda-beda untuk mencapai tujuan tersebut. Penelitian ini menyajikan analisis teori yang dilakukan terhadap landasan, proses, dan pengaruh Extraordinary Chambers in the Courts of Cambodia (ECCC). Pertama-tama, penelitian ini meninjau gagasan mengenai analisa terhadap pengadilan hibrida sebagai cara untuk mengatasi kendala yang dihadapi oleh mekanisme pengadilan pidana di masyarakat pascakonflik, dan kedua, mengeksplorasi apa yang disebut “Pengadilan Khmer Rouge”. Karena signifikansi dan kontroversi yang menyelubungi ECCC, karyanya menerima perhatian yang besar. Tekad secara politis sangat penting, sehingga pengadilan hibrida ini dapat memperoleh dukungan internasional lebih banyak dalam hal sarana politik, dana, penyebaran hasil, dan mekanisme untuk melengkapi keadilan transisional.